Effect of Diabetes Mellitus on Successful Treatment of Tuberculosis in Tanah Kalikedinding PHC - Zeni Yanti (Universitas Airlangga, 2017)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Surabaya City is one of the cities with the highest TB case in East Java. Achievement of Success Rate (SR) of Surabaya city in 2015 was 79.21% which is below the SR national standard (85%). The achievements of SR in the Public health center (PHC) of Tanah Kalikedinding have decreased each year. One of the causes of low SR achievement is the failure of TB treatment. This study aims to determine the effect of Diabetes Mellitus (DM) on the success of TB treatment. This study was an observational study with cross-sectional study design. This research was conducted at the PHC of Tanah Kalikedinding Surabaya in November 2016 - January 2017. The independent variable studied was DM, while the dependent variable was the success of pulmonary TB treatment. The total sample studied based on the calculation of the Slovin formula is 55 samples taken using systematic random sampling. Data analysis uses frequency distribution tables and logistic regression tests. The results showed that the majority of pulmonary TB patients in the PHC of Tanah Kalikedinding Surabaya were 45-55 years old (31%), female (55%), had a senior high school education (47.3%), and had no history of DM during pulmonary TB treatment (67.3%). The logistic regression test results showed that there was an influence between DM on the success of pulmonary TB treatment in PHC of Tanah Kalikedinding Surabaya (p = 0.012; OR = 2.056). DM screening at the beginning of TB treatment, giving proper treatment, and treatment monitoring are steps that can be done by the PHC of Tanah Kalikedinding Surabaya to minimize the incidence of TB treatment failure with DM.